Signatures of Ideology: The Case of the Supreme Court's Criminal Docket - Farnsworth, Ward (2005)
Everyone suspects that Supreme Court justices' own views of policy play a part in their decisions, but the size and nature of the part is a matter of vague impression and frequent dispute. Do their preferences exert some pressure at the margin or are they better viewed as the mainsprings of decision? The latter claim, identified with legal realism, has been lent some support by political scientists who point out that some justices regularly vote for or against certain kinds of claims (for example, under the Fourth Amendment), or that votes in some areas are broadly predictable according to a single ideal point that tries to sum up each justice's preferences, or that justices who dissent from a decision often will not acquiesce to it in future cases. The reason these studies haven't made much of an impression in the legal academy probably is that lawyers and scholars sense many reasons why judges' behavior may follow predictable patterns, not all of them related to their own preferences. Some justices may have ideas about interpretation that happen to produce outcomes friendly to one side or another as byproducts; and a judge's public reputation as a conservative or liberal, to which some of the political science work gives weight in explaining votes, likewise might arise because the judge's interpretive approach happens to yield results that conservatives or liberals like. A closer look is needed at judicial behavior in cases where the policy stakes are similar but the sources of interpretive dispute are different, the better to reveal which dominates which. The best set of such cases is found on the Supreme Court's criminal docket. Cases involving accused or convicted criminals raise all sorts of legal issues but can be seen to involve a common set of policy stakes: the courts have to referee disputes, often of a zero-sum character, over the advantages to be enjoyed by the government and the accused or convicted defendant. Of course one also can divide up criminal cases into narrower categories that may involve different policies; we will try it later. But the hypothesis that all such cases involve similar rough trade-offs as a matter of policy is a useful starting point. It gives us many decisions to study; cases about criminals usually take up around a third of the Court's docket every term, which is enough to support interesting statistical inquiries and generalizations